PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATERI IPAS PESERTA DIDIK KELAS IV SD NEGERI BAYAN - Budiarti, Anis; Anjarini, Titi; Suyoto, Suyoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Anis Budiarti. "Implementation of the Think Pair Share Type Cooperative Learning Model to Increase the Activeness and Learning Outcomes of Science Material for Class IV Students at Bayan State Elementary School." Thesis. Primary teacher education. FKIP, Muhammadiyah University Purworejo.2026. This research aims to 1) determine the implementation of teacher learning activities and student activities, 2) determine the increase in activeness and 3) the learning outcomes of students' science material through the think pair share model. The type of research used is PTK using a think pair share type cooperative model. The research subjects were class IV students at Bayan State Elementary School for the 2025/2026 academic year with a total of 25 students. Data collection techniques: observation, interviews, tests, documentation. Data collection instruments: interview sheets, activity observation sheets, learning implementation sheets for teacher activities and student activities, test sheets, documentation. The results of this research are 1) In cycle I, the implementation of educator activities was 63% to 72%, an average of 67.5%. In cycle II, 83% became 94%, an average of 88.5%. In the implementation of student activities at meeting I, 40% rose to 54%, an average of 47%. In cycle II, 78.5% rose to 90%, an average of 84.3%. 2) In pre-cycle activity, it was 37%, cycle I rose to 42.08%, and cycle II rose to 82%. The result is an increase in the percentage of activity by 39.2%. 3) The pre-cycle learning outcomes obtained an average of 50, the first cycle averaged 60.8 and the second cycle averaged 86. So, student learning outcomes increased from cycles I and II by 25.2. Thus, the application of the think pair share type cooperative model can increase the activity and learning outcomes of class IV at SD Negeri Bayan.